DESIGN AND FABRICATION OF LOW PROFILE MULTIBAND SLOTTED FRACTAL ANTENNA FOR BROADBAND COMMUNICATION SYSTEMS - Arshad Wahab,; Bilal Ahmad,; Waleed Ahmad,; Dr. Muhammad Kashif Khattak,; Aamir Hayyat,; Muhammad Shafique, (Spectrum of Engineering Sciences, 2025)
The Antennas required for modern communication devices should be compact in size. It must have low profile, increased efficiency, high bandwidth and high gain. To achieve the above-mentioned advantages; fractal antenna is a better choice because of its high bandwidth, high gain, efficiency, cost effectiveness, fabrication process and the size (physically small and electrically large). The proposed antenna design is composed of circular slots in rectangular patch of dimension (44 x 44) mm2 using FR4 substrate of thickness 1.6mm. The dimensions of the patch, substrate and ground are same. The antenna is simulated and fabricated in three iterations. The characteristics of the antenna are analyzed by co-polarization of E-plane and H-plane of measured radiation patterns in final iteration. The improvement in reflection coefficient is selected by changing the length of the micro strip fed line to different values of (17 – 20) mm. The antenna has wide bandwidths of (2 – 3.8) GHz and the scattering parameter of - 15.7dB at the resonance frequency of 2.4GHz in the first iteration. It covers the bandwidths of ISM, Bluetooth, WiMAX, WiBro and WLAN applications. The final iteration of antenna has the band widths of (2.2 – 3) GHz, (5.15 – 5.32) GHz and (8.2 to 8.8) GHz and suitable for WiMAX, WiBro, WCDMA, ISM, LTE, UMTS 11 and Bluetooth devices. The simulated gains of the antenna are 3.68dBi, 5.57dBi and 6.47dBi at the resonance frequencies of 2.4GHz, 5.2GHz and 8.2GHz. The simulated and measured radiation patterns are nearly omnidirectional. The proposed antenna is simulated by using CST and fabricated in three iterations. The different parameters such as the radiation patterns, the scattering parameters, and the variation in length of micro strip fed line and their effect on reflection coefficient, voltage standing wave ratio and current distribution in the radiating patch are analyzed and compare both the results.